Exact separation theorem for closed sets in Asplund spaces. (3rd July 2017) - Zheng, Xi Yin; Yang, Zhuowei; Zou, Jiangqian
Abstract: In this paper, in terms of the Fréchet normal cone, we establish exact separation results for finitely many disjoint closed sets in an Asplund space, which supplement the extremal principle and some fuzzy separation theorems. As an application, we provide a new optimality condition for a constraint optimization problem in terms of Fréchet subdifferential and Fréchet normal cone.